Exploring English speaking anxiety among Filipino engineering students: its influence on task performance and its sources - Quinto, Edward Jay Mansarate; Macayan, Jonathan Veran (Penerbit Universiti Kebangsaan Malaysia, 2019)
The need for effective English speaking skills in engineering fields compels schools to innovate curricula that shall address the language skills of a ‘global engineer.’ The impact of engineering curricular reforms trickled down among students who contend with language learning anxiety, besides anxiety from mathematics and other technical courses. In this paper, the researchers explored English speaking anxiety among 162 engineering students in an engineering University in Manila, Philippines. A mixed-method, explanatory sequential design was used. This method combines the quantitative and qualitative approaches in investigating the phenomenon under study, i.e., English speaking anxiety. In the quantitative phase, the researchers used data from the speaking component of a self-developed scale and speaking performance scores yielded from an interactive English conversation task. Analysis revealed a significant negative relationship between speaking anxiety and speaking task performance, pointing to the debilitative influence of anxiety on task performance. In the qualitative phase, semi-structured interviews among nine purposefully selected students revealed that both peers and teachers were common sources of speaking anxiety and in a variety of ways. The findings point to speaking anxiety as an important psycho- and sociolinguistic phenomenon, which is hinged on the specific roles that language teaching and learning plays in preparing engineering students as future language consumers and users in highly technical, specialized, and competitive engineering fields.